2010
DOI: 10.1111/j.1365-2125.2010.03755.x
|View full text |Cite
|
Sign up to set email alerts
|

Methodological characteristics of academic clinical drug trials – a retrospective cohort study of applications to the Danish Medicines Agency 1993–2005

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• WHAT THIS STUDY ADDS• Our study shows that randomization, definition of primary endpoint, monitoring according to the principles of Good Clinical Practice (GCP monitoring), and control of medicine compliance form part of a significantly increasing percentage of academic clinical drug trials. This indicates an increasing quality of these trials.• However, high numbers of unblinded randomized controlled trials and randomized controlled trials utilizing unacceptable meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…Since some of these instruments have been actually devised to guide reporting of clinical trials, this precluded their use in toto to assess quality of trial protocols, the principle focus of our study. These selected criteria have been previously utilized in studies and are considered critical for deriving conclusions from research findings that are meaningful to actual clinical practice (26,27). A scoring method comprising of both methodological characteristics based on the design of study as well as concordance with GCP guidelines was used in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since some of these instruments have been actually devised to guide reporting of clinical trials, this precluded their use in toto to assess quality of trial protocols, the principle focus of our study. These selected criteria have been previously utilized in studies and are considered critical for deriving conclusions from research findings that are meaningful to actual clinical practice (26,27). A scoring method comprising of both methodological characteristics based on the design of study as well as concordance with GCP guidelines was used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Berendt et al has demonstrated similar improvement trends in the reporting of primary outcomes in academic clinical trial applications submitted to drug regulatory authority. The study showed an improvement from 60% protocols reporting primary/secondary endpoints in 1995 to 92% in 2005 (27). The study examined the impact of European Clinical Trials Directive introduced in 2004.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some years ago we appealed for review papers about methods to study drug effects quantitatively. This appeal has not yet yielded a flood of papers but there has been a gratifying increase during 2010 [1,[3][4][5][6][7][8][9] and we hope that we will be able to refer to several more next year in our Editors' pick for 2011. While clinical pharmacologists have been closely involved for decades in the evaluation and monitoring of adverse drug reactions, a far more recent buzzword has been 'patient safety' .…”
Section: Risk/safety Assessmentmentioning
confidence: 99%